The Influence of Product Reviews, Prices and Trust on Online Purchase Decisions at Shopee - Telli Poniman Chandra; Anny Nurbasari (Indonesian Journal of Multidisciplinary Science, 2022)
The digital industry in Indonesia is growing and increasing very rapidly, one of the growing industries is the e-commerce industry in Indonesia. Trust, researchers conducted research on Shopee. So this research is entitled "The Influence of Product Reviews, Prices and Trust on Online Purchasing Decisions on Shopee In Bandung". In this study, the population consisted of customers in Bandung who had used the Shopee program for online shopping and the exact number was not known. The sample technique used is purposive sampling, with respondents consisting of Bandung residents who have used the Shopee program at least three times for online purchases. This research was conducted in Bandung. The investigation stage lasted for six months. There are independent factors and dependent variables in this study. Product reviews, cost and trust are independent factors. Whereas the bound variable is the option to buy. According to the research findings, product reviews do not affect purchasing decisions on Shopee. Shopee buyers are affected by the price when making a purchase. Shopee's purchasing decisions are influenced by consumer trust, Product Reviews, Pricing, and Trust all have an effect on the Purchase Decision.